1995
DOI: 10.3109/00365519509089620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged tourniquet ischaemia and short-term venous stasis on plasma endothelin-1 levels in man

Abstract: In vitro studies have indicated increased endothelial release of endothelin during tissue and cellular hypoxia. Therefore, we studied the effect of tourniquet ischaemia and venous stasis on plasma endothelin-1 (ET-1) levels in humans in vivo. The effect of hypoxia on plasma ET-1 levels in 16 patients subjected to an orthopaedic operation and six healthy volunteers was studied by (a) tourniquet ischaemia, in which a limb is totally emptied of blood and kept ischaemic by means of a pneumatic tourniquet, and (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…39 It is possible that, at least in some patients, increased basal ET-1 circulating levels could directly promote or favour vascular retinal occlusions, or otherwise reflect a baseline condition predisposing to RVO. However, findings from our study better fit a scenario in which the ET-1 plasma increase may represent a marker of the occlusion, possibly as a “spillover” phenomenon from a locally activated system 41. This possibility is supported by several lines of evidence.…”
Section: Discussionsupporting
confidence: 82%
“…39 It is possible that, at least in some patients, increased basal ET-1 circulating levels could directly promote or favour vascular retinal occlusions, or otherwise reflect a baseline condition predisposing to RVO. However, findings from our study better fit a scenario in which the ET-1 plasma increase may represent a marker of the occlusion, possibly as a “spillover” phenomenon from a locally activated system 41. This possibility is supported by several lines of evidence.…”
Section: Discussionsupporting
confidence: 82%
“…[33][34][35][36][37][38][39] Previous studies have demonstrated that the development of extended areas of nonperfused capillaries after BRVO in humans correlates with the secondary constriction of the arteriole that crosses the occluded area. 40 Arteriolar constriction of the apparently nonaffected arterioles irrigating the territory of the occluded veins occurs within hours of the occlusive phenomenon and can persist for months.…”
Section: Discussionmentioning
confidence: 98%
“….Ebenso war es uns aus medizinisch-ethischer Sicht nicht möglich, eine entsprechende Kontrollgruppe gesunder Probanden zu rekrutieren, denen man im Rahmen einer Operation zusätzlich ein Tourniquet mit vergleichbaren Ischämiezeiten hätte anlegen müssen, um zu statistisch verwertbaren Ergebnissen zu kommen. Dies könnte zudem erklären, warum es bisher nur einige vergleichbare Arbeiten mit ähnlichem Studiendesign gibt[10,13].Die Etablierung von Endothelin-1 als laborchemischen Parameter zur präoperativen Beurteilung drohender Zirkulationsstörungen bei der Latissimus dorsi-Transplantation ist aufgrund unserer Ergebnisse nicht sinnvoll.Bereits Sokolovsky[21] ließ im Ausblick zu seiner Arbeit erkennen, dass es schwierig sein werde, die Rolle für freies und lokal wirksames ET-1 exakt zu unterscheiden. Er verweist ebenso auf den medizinisch-ethischen Aspekt wie auf den nicht nachgewiesenen Zusammenhang erhöhter ET-1-Konzentrationen und biologischer Aktivität im Rahmen verschiedener Krankheitsprozesse.…”
unclassified